Evaluation of healthcare networks by nurses in the Family Health Strategy - Danusa da Silva Cabral; Murilo César do Nascimento; Talita Prado Simão Miranda; Sinézio Inácio da Silva Júnior; Flávio Bittencourt; Simone Albino da Silva (SciELO, 2020)
Abstract Objective: To evaluate the capacity of Primary Healthcare to coordinate healthcare networks. Method: A cross-sectional, population-based and descriptive study developed in the State of Minas Gerais through interviews with nurses working in the Family Health Strategy Sector (FHS) of the Unified Health System, using the Network Coordination Assessment Tool for Primary Healthcare. A descriptive statistical analysis was applied by implementing Fisher's exact test, Spearman's correlation coefficient and cluster analysis. Type I error was fixed at 5% for statistical significance. Results: There were 49 nurses interviewed, evaluating the population and primary healthcare dimensions as excellent. Support, logistical, governance and overall assessment systems were classified as having good condition in the network coordination for Primary Healthcare. The dendograms showed that the work process has similarities between Nurses, as well as the structure between the municipalities. Conclusion: Primary Healthcare has the ability to coordinate networks, constituting a process in which nurses have a central role. There were similarities in the work processes between evaluated municipalities and a deficit in information and pharmaceutical assistance systems.